A unusual case of 356 vesical calculii - Agarwal, A; Sigdel, G; KC, SR; Shrestha, P; Belokar, WK (Journal of College of Medical Sciences-Nepal, 2012)
Multiple vesical calculi are rarely seen in urological practice. Males are affected more than the females. Vesical calculi are usually secondary to bladder outlet obstruction. These patients present with recurrent urinary tract infection, haematuria or with retention of urine. We report a 43 years male patient who presented with acute urinary retention. He had history of trauma over perineal region three years back following which he had recurrent urinary tract infection and thinning of stream. USG abdomen revealed normal upper urinary tract with echogenic debris in partially filled urinary bladder. Renal function test was with in normal limit. Per urethral catheterization failed and over antibiotic cover, patient was posted for cystourethroscopy followed by suprapubic cystostomy under spinal anaesthesia. Membranous urethral stricture found during urethroscopy could be managed by optical internal urethrotomy. On cystoscopy whole of bladder was filled with thick pus like material with multiple large urinary bladder calculi. Open cystolithotomy was done and we were surprised to see 356 stones of various size and shape after removal. Patient made uneventful recovery and discharged after 12 days of hospital stay. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 44-47 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6825